Preclinical evaluation of scorzonera sp root extracts and major compounds against acute hepatotoxicity induced by carbon tetrachloride - Özbek, Hanefi; Bahadır Acıkara, Özlem; Keskin, İlknur; Kırmızı, Neriman İpek; Yiğitbaşı, Türkan; Sakul, Ayşe Arzu; İşcan, Gülçin Saltan (Wolters Kluwer Medknow Publications, 2017)
Evaluation of hepatoprotective activities of Scorzonera roots and their major compounds, was aimed in current study. Scorzonera latifolia, S. tomentosa, S. mollis ssp. szowitsii, S. parviflora and S. cana var. jacquiniana roots, methanol-water (80:20) extracts together with chlorogenic acid, scorzotomentosin-4'-O-beta-glucoside, hydrangenol-8-O-beta-glucoside as major compounds isolated from S. latifolia roots were tested for their hepatoprotective activities. Sprague Dawley rats were used for experiment and hepatotoxicity was induced by carbon tetrachloride. Aspartate aminotransferase and alanine aminotransferase levels were measured and all results were confirmed by histopathological examination. Plasma aspartate aminotransferase and alanine aminotransferase levels of examined groups were not significant when compared to carbon tetrachloride-treated groups. However histopathological results have revealed that all tested groups have less damage when compared to carbon tetrachloride group except scorzotomentosin-4'-O-beta-glucoside and hydrangenol-8-O-beta-glucoside groups. Scorzonera species displayed moderate hepatoprotective activities against carbon tetrachloride induced acute toxicity. Chlorogenic acid, among tested compounds exhibited higher activity than all tested Scorzonera species as well as other isolated compounds. Therefore chlorogenic acid could be suggested as responsible compound.
WOS: 000419284200007
Keywords: Scorzonera Sp.; Hepatoprotective Effect; Carbon Tetrachloride; Chlorogenic Acid